Error Analysis on the Use of Noun Article: A Case Study of a Second Language Learner in the U.S. - Sidarta Prassetyo (Universitas Airlangga, 2016)
The present study examines error analysis of second language learner of English. It aims to describe the errors made by the learner especially in her written production and to explain the reasons why the errors occur. The focus of explaining the error is the use of article since the article has been widely known to be one error often found in the L2 learners. Cloze tests (filling in the blanks), multiple choice questions, essay writing (the participant was asked to write a 250 word essay), and in-depth interview were conducted to collect the data from the participant. In addition, observation on the learner’s performance for oral production was also conducted. The learner’s native languages are Javanese and Indonesian language. She has been exposed to English language since she was the fourth grader, but she admits that writing is difficult for her. The result of analysis found that the learner indeed made error in the use of article, and she inconsistently used the article and the nouns that follow the article. It happened because of interlingual transfer (negative transfer from L1 to L2) and intralingual transfer in which she made false analogy and misanalysis on the second language.